2005
DOI: 10.1016/j.apacoust.2004.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Performance of profiled single noise barriers covered with quadratic residue diffusers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 13 publications
2
44
0
1
Order By: Relevance
“…Barrier caps, in theory, allow improving barriers already put in place (retrofitting). Complex shapes have been studied and optimized before [20][21][22][23][24][25]. To study the improvement in performance by adding absorbing caps, three basic shapes were numerically evaluated with a 2D-BEM technique in Ref.…”
Section: Noise Walls With Vegetated Capsmentioning
confidence: 99%
“…Barrier caps, in theory, allow improving barriers already put in place (retrofitting). Complex shapes have been studied and optimized before [20][21][22][23][24][25]. To study the improvement in performance by adding absorbing caps, three basic shapes were numerically evaluated with a 2D-BEM technique in Ref.…”
Section: Noise Walls With Vegetated Capsmentioning
confidence: 99%
“…This was already explained for quadratic residue diffuser edge barrier by Monazzam and Lam (2005). It seems that the diffuser surface redirects some of the sound wave upward, hence the low performance of the diffusive barrier is expected at these zones.…”
Section: Sequence Effectmentioning
confidence: 94%
“…Fujiwara et al (1998) has shown that a uniform series of rigid wells in the upper surface of a T-shape barrier produces insertion loss values equal to those of a soft surface over a significant range of frequencies. In respect to the use of Quadratic Residue Diffuser (QRD) to cover the top of the barrier, Monazzam and Lam (2005) has shown that a T-shape barrier design produces a higher barrier A-weighted insertion loss than using a typical fibrous absorbent material on the barrier. A similar type of examination for T-shape barriers is shown in Baulac et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, an equivalent frequency of 550 Hz can be set to represent the total frequency band in the calculation of diffraction suggested in the FHWA traffic noise model [27]. In the 1/3rd-octave-band spectrum, the frequency of 500 Hz is used in the approximate calculation of diffraction and noise reduction effect of a sound barrier [9,[28][29][30][31]. However, the data used was collected from 1993 and 1995, and the characteristics of vehicle noise have changed since then because of the variety of vehicle types and speeds [32].…”
Section: Introductionmentioning
confidence: 99%
“…Current research on noise barriers primarily focuses on noise calculation [8,9], the effects of barrier shapes [10,11], and the design of barriers [12][13][14][15]. As one of the important aspects, prediction of the insertion loss by the noise barrier has been attracting the attention of scholars, and both mathematical and experimental approaches have been developed.…”
Section: Introductionmentioning
confidence: 99%